Understanding Infection-Induced Thrombosis: Lessons Learned From Animal Models - Beristain-Covarrubias, Nonantzin; Perez-Toledo, Marisol; Thomas, Mark R.; Henderson, Ian R.; Watson, Steve P.; Cunningham, Adam F. (Frontiers in Immunology, 2019)
Thrombosis is a common consequence of infection that is associated with poor patient outcome. Nevertheless, the mechanisms by which infection-associated thrombosis is induced, maintained and resolved are poorly understood, as is the contribution thrombosis makes to host control of infection and pathogen spread. The key difference between infection-associated thrombosis and thrombosis in other circumstances is a stronger inflammation-mediated component caused by the presence of the pathogen and its products. This inflammation triggers the activation of platelets, which may accompany damage to the endothelium, resulting in fibrin deposition and thrombus formation. This process is often referred to as thrombo-inflammation. Strikingly, despite its clinical importance and despite thrombi being induced to many different pathogens, it is still unclear whether the mechanisms underlying this process are conserved and how we can best understand this process. This review summarizes thrombosis in a variety of models, including single antigen models such as LPS, and infection models using viruses and bacteria. We provide a specific focus on Salmonella Typhimurium infection as a useful model to address all stages of thrombosis during infection. We highlight how this model has helped us identify how thrombosis can appear in different organs at different times and thrombi be detected for weeks after infection in one site, yet largely be resolved within 24 h in another. Furthermore, we discuss the observation that thrombi induced to Salmonella Typhimurium are largely devoid of bacteria. Finally, we discuss the value of different therapeutic approaches to target thrombosis, the potential importance of timing in their administration and the necessity to maintain normal hemostasis after treatment. Improvements in our understanding of these processes can be used to better target infection-mediated mechanisms of thrombosis.